2018
DOI: 10.5578/tt.67689
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances in patients with lung cancer in Turkey

Abstract: Sonuç: Çalışmamız, kanser semptomları ile uyku kalitesi arasında yakın bir ilişki olduğunu ortaya koymuştur. Bu nedenle, akciğer kanserli hastalarda kaliteli bir uyku için, kanser semptomların yeterince kontrol edilmesi gereklidir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
2
7
2
Order By: Relevance
“…Patients with moderate to severe severity pain, dyspnea, and anxiety were independently related to insomnia. 23 Taken together, this information is consistent with data of the that sleep deprivation, fragmentation and hypoxia negatively predict survival shining light on the role of sleep on the innate and adaptive immune systems. [24][25][26] The study has some limitations due to the nature of a crosssectional design.…”
Section: Discussionsupporting
confidence: 82%
“…Patients with moderate to severe severity pain, dyspnea, and anxiety were independently related to insomnia. 23 Taken together, this information is consistent with data of the that sleep deprivation, fragmentation and hypoxia negatively predict survival shining light on the role of sleep on the innate and adaptive immune systems. [24][25][26] The study has some limitations due to the nature of a crosssectional design.…”
Section: Discussionsupporting
confidence: 82%
“…As reported in previous studies, sleep disturbance was focused on patients with breast cancer, and the incidence of sleep problems ranged from 39.5 to 69% (19,23). However, other studies showed that patients with lung cancer had the poorest sleep quality compared with other cancer types or control populations (24,25). A similar result was found in the cureent study that patients with lung cancer had the highest proportion of sleep disorders (45.2%) before radiotherapy compared with other cancer types.…”
Section: Discussionmentioning
confidence: 93%
“…Most studies focused on sleep problems in patients with cancer, and the probabilities of sleep disturbance in different tumor subtypes showed significant discrepancies (19,(23)(24)(25)(26). As reported in previous studies, sleep disturbance was focused on patients with breast cancer, and the incidence of sleep problems ranged from 39.5 to 69% (19,23).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Nishiura et al found a prevalence of 56% in lung cancer patients who were admitted to hospital or already in-patients, regardless of the type of treatment (14). In addition, Bülbül et al reported rates of 48.4% for difficulty initiating or maintaining sleep (DIMS) and of 44.7% for insomnia in a large unspecified cohort of 1,245 patients with lung cancer (15).…”
Section: Discussionmentioning
confidence: 99%